PENGARUH PERENCANAAN PAJAK. ASET PAJAK TANGGUHAN, DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR TERDAFTAR DI BURSA EFEK INDONESIA 2017 - 2020 - Juliani, Juliani; Astuti, Titiek Puji; Suseno, Agus Endrianto (ITB AAS INDONESIA, 2023)
This study aims to examine tax planning, deferred tax assets, deferred tax expense on earnings management. The type of research used is quantitative with secondary data taken from the IDX. The analytical method used is panel data regression analysis with Eviews9 software. The population of this study uses manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 – 2020. The research sample uses the purposive sampling method so that a total of 158 company data are obtained. The results of research testing have a conclusion that tax planning has a negative effect on earnings management. Deferred tax assets have a positive effect on earnings management. Deferred tax expense has a positive effect on earnings management. Keywords : Tax Planning, Deferred Tax Assets, Deferred Tax Expense, Earnings Management